Study of Motivation to Play Video Games in the 90s Generation Using the Gamer Motivation Model - Afif, Muhammad; Grahita, Banung (Gorga : Jurnal Seni Rupa, 2024)
The 1990s were a pivotal era for the development of video game consoles, significantly influencing the gaming preferences and habits of the 90s generation, often referred to as digital natives. This research investigates the motivations behind why individuals from this generation engage in video gaming, utilizing the Gamer Motivation Model as a framework. The study involved interviews with 9 respondents from the 90s generation who are actively involved in gaming. The findings highlight that the primary motivations for these gamers are driven by the desire for Completion and the thrill of Excitement during gameplay. Players find satisfaction in collecting items, completing missions, and reaching milestones within games, which serve as key motivators. Furthermore, they are drawn to dynamic gaming experiences that are rich with surprises, providing emotional highs and adrenaline boosts that enhance the overall gaming experience. In addition to these primary motivations, the research also delves into secondary motivations, exploring other factors that contribute to the gaming experience for this demographic. The insights gained from this study are valuable for both researchers and game developers, as they provide a deeper understanding of the specific gaming motivations of the 90s generation. This understanding can be leveraged to design gaming experiences that are more closely aligned with the preferences and needs of this group.